A Review of Drug Abuse, Misuse, and Related Laboratory Challenges - Ranjkeshzadeh, Haniye; Sepahi, Samaneh; Zare-Zardini, Hadi; Taghavizadeh Yazdi, Mohammad Ehsan; Ghorani-Azam, Adel; Jafari, Abbas (Current Drug Safety, 2024)
Various definitions can be considered for drugs and substance abuse. According to the National Institute on Abuse, the use of an over-the-counter drug in a different way than that prescribed to experience or arouse emotion is a simple form of drug abuse. The World Health Organization (WHO) also defines drug abuse as the persistent or sporadic use of drugs that are incompatible or unrelated to acceptable medical practice. With the increasing non-therapeutic use of prescription drugs, serious related consequences have also increased. Therefore, there is a need to know more precisely about the types of substances and drug abuse, which is the most important part of diagnosis and recognizing the tests that cause false positive and negative results. The purpose of this review article is to collect and summarize the most important and more common types of drugs of abuse and review the drugs that cause false results in screening tests. In addition, the most common detection methods of the drug will be reviewed and the advantages and drawbacks of each method will be discussed. In this article, we aimed to point out all the facts about the emerging problems in drug abuse, the methods of screening, and the possible false results in addition to troubleshooting strategies.
Keywords: narcotics